ANALISIS INDEKS KEKERINGAN METEOROLOGIS MENGGUNAKAN METODE STANDARDIZED PRECIPITATION INDEX DI KABUPATEN PELALAWAN - Yogi Guntara; Sigit Sutikno; Lita Darmayanti (Racic : Rab Construction Research, 2023)
Drought is one of the natural phenomena indicated by the limited availability of water above, on the surface and in the ground. Pelalawan District has a history of drought which occurred in 2015 and resulted in a water crisis. Drought index measurement with the help of spatial techniques is often the key in assisting monitoring to determine drought prevention measures. This study conducted a spatial analysis to determine the distribution of drought using the Standardized Precipitation Index (SPI) method a 3-month time scales. This research used monthly satellite rainfall from 2010-2019. The results of the analysis show that extreme drought conditions occurred in June 2015 in Kuala Kampar sub-district with a value of -3.70.